Applying social cognitive theory to placement learning in business firms and students' entrepreneurial intentions. Issue 1 (March 2022) - Nwosu, Hyginus Emeka; Obidike, Paul C.; Ugwu, Joy Nonyelum; Udeze, Chimeziem C.; Okolie, Ugochukwu Chinonso
Abstract: Building upon the social cognitive theory, this study examines the environmental and person factors that influence students' entrepreneurial intentions. Also, it examines the mediating effect of entrepreneurial self-efficacy and entrepreneurial creativity, and the moderating effect of entrepreneurial passion on placement learning in business firms and entrepreneurial intentions. Using time-lag data from 273 university students who had completed the placement learning programme in 71 business firms, we test the moderated mediation model. Findings indicate that the conditional indirect effect of placement learning in business firms on students' entrepreneurial intentions via entrepreneurial self-efficacy was significant and contingent upon the level of students' entrepreneurial passion (-1SD, Mean and +1SD), whereas, the conditional direct effect on students' entrepreneurial intentions was only contingent on entrepreneurial passion only on the average and high levels. Our study progresses the principles of social cognitive theory and links placement learning in business firms and entrepreneurial intentions. Highlights: We examined effect of placement learning in business firms on students' entrepreneurial intentions. Placement learning in business firms predicted students' entrepreneurial intentions. We tested a moderated mediation model of placement learning in entrepreneurship context. Entrepreneurial self-efficacy and entrepreneurial creativity mediated the relationship. Entrepreneurial intentions strengthened the mediated relationship.